Extended analysis of FTIR high resolution spectra of HD32S and HD34S in the region of the ν2 band: Positions and strengths of individual lines. (March 2019) - Sydow, C.; Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Xintong, Zhou; Glushkov, P.A.; Maul, C.; Bauerecker, S.
Highlights: High resolution analysis of HDS FTIR spectra. The v 2 band: line positions and strengths. Determination of spectroscopic parameters. Abstract: The high resolution infrared spectra of deuterated hydrogen sulfide HDS were recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer (Zurich prototype ZP2001) and analyzed in the ν 2 fundamental band region, 690–1510 cm − 1 . 2684 transitions with maximum values of the quantum numbers J max = 25 and K a max = 17 were assigned in the experimental spectra to the ν 2 band (compared to J max = 22 and K a max = 10 in the preceding analogous studies) of HD 32 S. On this basis, 415 upper ro–vibrational energies were obtained, which were used then in the weighted fit of the Watson Hamiltonian parameters. 33 parameters obtained from the fit reproduce the 415 initial energy values with a root mean square deviation d r m s = 1.1 × 10 − 4 cm − 1 . An analysis of 418 experimental ro–vibrational line intensities of the ν 2 band of HD 32 S was made using the Hartmann–Tran profile of individual lines, and results were applied in the fit of parameters of the effective dipole moment operator. Isotopic relations for the dipole moment parameters were derived and used for the fit procedure. The obtained "model" parameters reproduce the initial line strengths with the d r m s = 4.7 % . A list of 2684 experimental transitions of HDS is generated together with the presentation of their individual line strengths predicted on the basis of the obtained effective dipole moment parameters. An analogous analysis was fulfilled for the ν 2 band of the HD 34 S isotopologue.